PENGGUNAAN TEKNOLOGI DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Syahidaturrahma, Manzilah; Maknun, Lu’luil (PT. Jurnal Center Indonesia Publisher, 2024)
The purpose of this study is to find out how effective the use of technology-based learning media is in improving students' language skills in primary schools. Literature study was used as the methodology, and descriptive research was used by using library research projects such as Google Scholar to obtain comprehensive data for online or digital journals. In Indonesian language learning, technology has become a significant issue. The results show that technology in education is very important because it allows students to gain knowledge about learning materials, work efficiently, and understand complex materials so that they can overcome challenges. Teachers should plan and optimisestrategically to improve student outcomes.